(1) 证明: $p_1, p_2$ 为 $(E-A) x=0$ 的解, $p_3$ 为 $(E-A) x=-p_2$ 的解, 且 $\boldsymbol{A}$ 不可相似对角化;
(2) 当 $\boldsymbol{A}=\left[\begin{array}{ccc}2 & -1 & -1 \\ 2 & -1 & -2 \\ -1 & 1 & 2\end{array}\right]$ 时, 求可逆矩阵 $\boldsymbol{P}$, 使得 $\boldsymbol{P}^{-1} \boldsymbol{A} \boldsymbol{P}=\left[\begin{array}{ccc}1 & 0 & 0 \\ 0 & 1 & 1 \\ 0 & 0 & 1\end{array}\right]$

(1) 由题意知 $\boldsymbol{A P}=\boldsymbol{P}\left[\begin{array}{ccc}1 & 0 & 0 \\ 0 & 1 & 1 \\ 0 & 0 & 1\end{array}\right]$, 也就是 $\boldsymbol{A}\left(\boldsymbol{p}_1, \boldsymbol{p}_2, \boldsymbol{p}_3\right)=\left(\boldsymbol{p}_1, \boldsymbol{p}_2, \boldsymbol{p}_3\right)\left[\begin{array}{lll}1 & 0 & 0 \\ 0 & 1 & 1 \\ 0 & 0 & 1\end{array}\right]$ 由于 $\boldsymbol{A}\left(\boldsymbol{p}_1, \boldsymbol{p}_2, \boldsymbol{p}_3\right)=\left(\boldsymbol{A} \boldsymbol{p}_1, \boldsymbol{A} \boldsymbol{p}_2, \boldsymbol{A} \boldsymbol{p}_3\right),\left(\boldsymbol{p}_1, \boldsymbol{p}_2, \boldsymbol{p}_3\right)\left[\begin{array}{lll}1 & 0 & 0 \\ 0 & 1 & 1 \\ 0 & 0 & 1\end{array}\right]=\left(\boldsymbol{p}_1, \boldsymbol{p}_2, \boldsymbol{p}_2+\boldsymbol{p}_3\right)$ 所以 $\left\{\begin{array}{l}A p_1=p_1 \\ A p_2=p_2 \\ A p_3=p_2+p_3\end{array}\right.$, 即 $\left\{\begin{array}{l}(E-A) p_1=\mathbf{0} \\ (E-A) p_2=\mathbf{0} \\ (E-A) p_3=-p_2\end{array}\right.$ 所以 $p_1, p_2$ 为 $(E-A) x=0$ 的解, $p_3$ 为 $(E-A) x=-p_2$ 的解。

(2) 由 (1) 知 $\boldsymbol{E}-\boldsymbol{A}=\left[\begin{array}{ccc}-1 & 1 & 1 \\ -2 & 2 & 2 \\ 1 & -1 & -1\end{array}\right]$, 所以解 $(\boldsymbol{E}-\boldsymbol{A}) \boldsymbol{x}=\mathbf{0}$ 得 $\boldsymbol{x}=k_1\left[\begin{array}{l}1 \\ 1 \\ 0\end{array}\right]+k_2\left[\begin{array}{l}1 \\ 0 \\ 1\end{array}\right]$ 所以 $\left(\boldsymbol{E}-\boldsymbol{A},-\boldsymbol{p}_2\right)=\left[\begin{array}{cccc}-1 & 1 & 1 & -\left(k_1+k_2\right) \\ -2 & 2 & 2 & -k_1 \\ 1 & -1 & -1 & -k_2\end{array}\right] \stackrel{r}{\rightarrow}\left[\begin{array}{cccc}1 & -1 & -1 & -k_2 \\ 0 & 0 & 0 & -\left(k_1+2 k_2\right) \\ 0 & 0 & 0 & -\left(k_1+2 k_2\right)\end{array}\right]$ 于是 $k_1+2 k_2=0$ 时, $(\boldsymbol{E}-\boldsymbol{A}) \boldsymbol{x}=-p_2$ 有解。

①点击 首页查看更多试卷和试题 , 点击查看 本题所在试卷